SNP and haplotype characterisation of apobec 3G, a protein involved in retroviral defence, in Black South Africans - Ramdin, Roshilla (My University, 2013)
It is known that infectious agents elicit different responses in different individuals which strengthens the view that susceptibility and resistance to infectious diseases has a genetic component. These differences in susceptibility to disease can be observed in populations. APOBEC3G is a member of the cytidine deaminase gene family located on chromosome 22. It is crucial in non-permissive cells as it functions as part of the innate immunity system and is an inhibitor of the HIV-1 accessory protein vif. The goal of the study was to develop genotyping assays and estimate allele frequencies. Thus, genetic variation within APOBEC3G was identified and characterized in black South Africans. Indirect genotyping assays were designed to amplify regions within the upstream non-coding region, and in exon 4 of the coding region of the gene. Selected polymorphisms were then genotyped using allele-specific PCR, RFLP-PCR and Pyrosequencing™ assays. Reanalysis of sequence data from 2003 showed numerous SNPs were well represented. Comparison of sequence data at various SNPs showed that allele frequencies were similar to frequencies in other African populations. The only sequenced SNP that deviated from the frequencies in Ensembl was -590. Thus the sequencing was a useful tool for detection of variation. ASA proved to be the least reliable genotyping technique as the minor allele frequency of -571 (0.59) deviated from the published frequency of 0.894 in Africans. RFLP analysis proved more reliable for genotyping -571 and H186R. The minor allele frequency was estimated to be 0.84 and 0.32 for -571 and H186R respectively. The frequency of H186R is similar to published data from An et al (2004) and Reddy et al (2010). If SNPs are in LD they occur together on the same haplotype more often than by chance. Usually SNPs that are in LD are in close proximity. However our data suggests -571 and H186R SNPs which are 5kb apart are not in LD. A LD map of chromosome 22 shows highly variable pattern of LD (Dawson et al, 2002). Widespread regions of nearly complete LD up to 804 kb in length are intermingled with regions of little or uundetectable LD. Haplotype analysis showed the most frequent haplotype was GA. This was the most frequent haplotype when the sample types were subdivided according to spoken language. in comparison to studies from An et al, (2004) D’ of the two SNPs was estimated at 0.967. The linkage disequilibrium (LD) revealed a non-independence of allele segregation because the loci analyzed were strongly linked in the Apobec 3 G gene. The data are consistent with greater genetic diversity of African populations and can form the basis for further evaluation of the role of variation in this gene in response to HIV.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, in fulfillment of the requirements for the degree of Master of Science Johannesburg, August 2012
Keywords: Antiretroviral agents.; Haploidy.; HIV infections - Treatment - South Africa.